Composite design for a foiling optimist dinghy - Oddy, C.; Blomstrand, E.; Johansson, D.; Karlsson, N.; Olofsson, N.; Steen, P.; Fagerström, M.; Asp, L. E.; McVeagh, J.; Brown, M.; Finnsgård, C. (Proceedings, 2018)
In April 2017, a foiling Optimist dingy designed entirely by students, was successfully tested under standard sailing conditions in the waters outside Gothenburg. In order to achieve take of wind speeds as low as 6 m/s, a stiff and lightweight design of the dinghy and its foiling components was necessary. There have been few successful attempts to make an Optimist foil in a stable manner, as such there were no standards or recommendations available for the design. Therefore, a simulation driven structural design methodology for hydrofoils, centreboards, centreboard-to-hull connections, and necessary hull reinforcements using sandwich structures was adopted. The proposed design was then manufactured, allowing for a significantly stiffer hull and a 20% decrease in weight over a conventional Optimist. Excluding the rig and sail, the final weight came to 27 kg.